Zircon in sak lu'um: evidence of multiple eocene silicic tephra layers as palygorskite precursors in the Yucatán peninsula, Mexico - Cisneros de León, Alejandro; Schmitt, Axel Karl; Roberge, Julie (Journal of South American earth sciences, 2019)
The provenance and nature of palygorskite clay used by Mayas for the creation of the outstanding Maya Blue pigment and pottery in the Yucatán peninsula has not been analyzed thoroughly. Especially the hypothesis of palygorskite being a diagenetic product of volcanic glass has remained uncertain. Here, we present a detailed study of zircon extracted from palygorskite-rich materials (sak lu'um) collected in the interior of the Sacalum cenote and near Chapab village, to evaluate the potential of zircon as an indicator mineral for tephra-derived palygorskite or clay-rich deposits intercalated with carbonate rocks. U-Pb zircon geochronology and correlative trace element analyses from stratigraphically different palygorskite-rich horizons indicate a restricted Eocene age range, which is coeval to the deposition of the host carbonates, and discrete airborne emplacement events of silicic tephra into warm and shallow waters at ca. 50 Ma and 41Ma, likely derived from volcanoes in a continental magmatic arc. Our findings also indicate that palygorskite deposits in the Yucatán peninsula are not inherited from continental sources but rather formed in-situ partly from weathering of volcanic glass that sourced Si and Al required for palygorskite formation.
Gesehen am 11.07.2019